The Implementation of Gamification Using Wordwall for Speaking Practice at A Junior High School in Karawang - Rahayu, Karina Sri; Utami, Praditya Putri; Ridwan, Iwan (FKIP - Universitas Riau, 2025)
This study aimed to investigate the implementation of gamification using Wordwall as a tool to support students' speaking practice in an English class at a junior high school in Karawang. A qualitative case study design was employed to explore students’ experiences, challenges, and engagement. Data were collected through classroom observations and semi-structured interviews with five selected students actively participating in speaking activities. The findings indicated that Wordwall support students’ motivation, confidence, and collaboration during speaking practices. Furthermore, Wordwall’s interactive elements supported students’ comprehension and vocabulary usage. However, the study also identified several challenges, including limited vocabulary, fear of making grammatical mistakes, and pressure from game elements. In addition, Wordwall was considered as an appropriate gamification tool for support speaking engagement. The study concludes that gamified learning using Wordwall could benefit English speaking practice, especially in classroom with limited resources, and recommends its integration to support language development and collaborative learning.